Development of Self-Learning Media through Digital Literacy in Arithmetic Line Materials - Fitri Umardiyah; Ika Nur Amaliah (APPLICATION: Applied science in Learning Research, 2021)
This research aims to develop self-learning media through digital literacy in valid and practical arithmetic line materials. This research is a research of developers using ADDIE (Analysis, Design, Development, Implementation, and Evaluation) methods. The analysis technique of this study uses validity analysis in the form of score value from validator and teacher response value. And practicality analysis in the form of the value of students' response to self-learning media through digital literacy. The results of this study produced independent learning products through digital literacy. Product feasibility is obtained based on validation tests and practicality tests. Material expert assessments score 80% with a valid classification. The assessment of teacher questionnaire response got a score of 85% with a very valid classification. Based on these results, it can be concluded that self-learning media through digital literacy is feasible to be used.